Pengaruh Model Pembelajaran Flipped Classroom terintegrasi Cooperative Learning Terhadap Motivasi Siswa pada Materi Pelajaran Reaksi Reduksi dan Oksidasi - Rizka Amalia Rahmawati; Sukro Muhab; Tritiyatma Hadinugrahaningsih (LPPM Universitas Negeri Jakarta, 2020)
This study aims to determine the effect of flipped classroom integrated cooperative learning model toward students’ motivation on reduction and oxidation reaction. This study was conducted at SMAN 4 Tangerang in tenth graders of science. The method of the study is quasi experiment with nonequivalen control grup design. Students in experimental group used flipped classroom integrated cooperative learning model, mainwhile, students in control group used cooperative learning model. Based on the result of data analysis, there is a significant difference between students’ motivation in control group with the experimental group seen from tobs 1,77 > ttable 1,67 at the level of significance is 0,05, it can be concluded that there is a positive effect on the application flipped classroom integrated cooperative learning model toward students’ motivation on reduction and oxidation reaction. Keywords Flipped classroom, Cooperative learning, Motivation